Influence of supply chain management on the sustainable construction industry in Algeria - Harouache, Ahmed; Abkar, Mahdi Mohammed Abdullah; Gamil, Yaser; Al-Shameri, Ahmed Saleh Ahmed; Gabir, Adham Ahmed Mohammed (Frontiers Media SA, 2024)
The construction industry, a pivotal business sector facilitating physical infrastructure and equipment provision, holds a significant indirect influence on diverse industries. This study investigates the role of supply chain management in enhancing sustainable construction practices within the Algerian construction industry. The research delves into the relationship between traditional supply chain management and sustainable construction, employing a quantitative approach. Data collection involved a survey comprising 61 items, utilizing a five-point Likert scale, gathered through an online survey method targeting managers, supervisors, executives, and suppliers in the Algerian construction industry. With 237 participants from construction companies in Algeria, the study utilized Smart PLS for data analysis, confirming a positive relationship between traditional supply chain management and sustainable construction through partial least squares (PLS) path analysis. The findings provide valuable insights for future stakeholders, guiding employers, designers, manufacturers, contractors, and suppliers to enhance supply chain management practices for sustainable construction in Algeria. Consequently, this study offers significant results with practical and theoretical implications, contributing to the integration of sustainable supply chain management in Algerian construction. In summary, the research addresses the relationship challenges between traditional supply chain management and sustainable construction practices in Algeria.